A Rhetorical Analysis of Ustadz Felix Siaw's Da'wa on Youtube - Hamdani, Syaifullah; Japeri, Japeri; Yazan, Sheiful; Fauzi, Muhammad (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2022)
There are many aspects that make a da'i popular among mad'u, one of which is rhetoric. Rhetoric is a style of conveying messages conveyed by da'i to mad'u. By conveying a good message, it will raise the dignity and degree of the da'i. This study aims to determine Ustadz Felix Siauw's rhetorical style including language style, voice style, and gesture style. The method used in this study uses a qualitative research method with a content analysis approach. The data collection technique is observing or watching videos that have been uploaded on the